Erysipelas‐like erythema as the presenting feature of familial Mediterranean fever. (14th January 2012) - Lidar, M.; Doron, A.; Barzilai, A.; Feld, O.; Zaks, N.; Livneh, A.; Langevitz, P.
Abstract Background 'Erysipelas‐like' erythema (ELE) is a well recognized, although uncommon, manifestation of familial Mediterranean fever (FMF), which is frequently mistaken for infectious erysipelas, especially when forming the initial disease presentation. Aim To clinically and genetically characterize ELE as the first manifestation of FMF. Methods FMF patients with ELE as the first disease presentation (study group), were compared with FMF patients with ELE, appearing during the disease course (control group I), and to those FMF patients who never had ELE (control group II). Results Patients of the study group were comparable to patients without ELE with respect to all demographic, clinical and genetic features studied, and yet differed from patients with ELE appearing later in the disease course in disease severity score (1.7 ± 0.4 vs. 2.4 ± 0.6, P = 0.01), length of diagnosis delay (7.2 ± 6.4 vs. 2.3 ± 3.3 years, P=0.037), age of FMF onset (24.8 ± 19.9 vs. 5.6 ± 5.7 years of age, P=0.014) and rate of homozygosity to the M694V mutation (14.3% vs. 68.7% respectively). ELE traits in the study and control groups were alike. Conclusions FMF with ELE as the first disease manifestation form an uncommon subgroup, clinically and genetically diverging from the rest of the FMF‐ELE patients.